Expression analysis of circulating plasma long noncoding RNAs in colorectal cancer: The relevance of lncRNAs ATB and CCAT1 as potential clinical hallmarks. Issue 12 (15th May 2019) - Abedini, Paria; Fattahi, Azam; Agah, Shahram; Talebi, Atefeh; Beygi, Amir Hossein; Amini, Seyed Mohammad; Mirzaei, Alireza; Akbari, Abolfazl
Abstract: Long noncoding RNAs (lncRNAs) have been demonstrated to regulate a variety of cell processes and involve in the development and progression of colorectal cancer (CRC). Recently, the circulating lncRNAs have emerged as minimally invasive biomarkers for cancer diagnosis and prognosis. We aimed to examine the plasma expression level of long noncoding RNAs lnc‐ATB, lnc‐CCAT1, and lnc‐OCC‐1 in CRC patients and evaluate the clinical values. A total of 74 pretreatment CRC and 74 healthy blood biopsies were subjected to differentially evaluate the expression levels of three lncRNAs (OCC‐1, CCAT1, and ATB). Briefly, after plasma separation and total RNA extraction, RNAs were reversely transcribed to complementary DNA followed by amplification using a quantitative real‐time polymerase chain reaction technique for lncRNA expression analysis. The results showed that the expression levels of lnc‐ATB ( p  < 0.001) and CCAT1 ( p  = 0.024), but not OCC‐1 ( p  = 0.24), were significantly upregulated in the CRC compared with the healthy group. The calculated AUC of ROC was 0.78 (95% confidence interval [CI]: 0.811–0.94) for lnc‐ATB and 0.64 (95% CI: 0.811–0.94) for CCAT1, which were indicative of a high discriminatory power ( p  < 0.001). The highest accuracy for lncRNA‐ATB was obtained at a cutoff point of 2.5, which corresponded to sensitivity and specificity of 82% and 75%, respectively. Our results suggested a significant accuracy of lncRNA‐ATB and lncRNA‐CCAT1 in distinguishing CRC patients from healthy individuals. Abstract : We examined the plasma expression level of long noncoding RNAs lnc‐ATB, lnc‐CCAT1, and lnc‐OCC‐1 in colorectal cancer (CRC) patients and evaluate the clinical values. Our results suggested a significant accuracy of lncRNA‐ATB and lncRNA‐CCAT1 in distinguishing CRC patients from healthy individuals.